Legal Protection of Good Faith Buyers in Developer Bankruptcy: Indonesian Supreme Court Decision 24K/Pdt.Sus-Pailit/2025 - Dafa, M Naufal Abiyi; Sakti, Muthia (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
This study examines the legal protection afforded to good-faith housing buyers when objects of a Binding Sale and Purchase Agreement (PPJB) are included in a developer's bankruptcy estate, focusing on Supreme Court Decision No. 24 K/Pdt.Sus-Pailit/2025. The research employs a normative juridical method, using statutory, conceptual, and case approaches to analyze bankruptcy law, consumer protection norms, PPJB regulations, and judicial reasoning. The study finds that although the PPJB in the case was privately executed and did not comply with the formal requirements of Ministerial Regulation ATR/BPN No. 16 of 2021, the Supreme Court affirmed that buyers who had fully paid and taken possession before bankruptcy qualify as good-faith third parties entitled to protection. The Court emphasized the asset separation principle, holding that only assets legally owned by the debtor at the time of bankruptcy may form part of the bankruptcy estate, thereby limiting the universality principle and prioritizing substantive justice. By annulling the curator’s action, the decision strengthens consumer protection in developer bankruptcy cases. This study concludes that buyers require both preventive and repressive legal protection, and that PPJBs should be executed as authentic deeds with a power of sale clause to prevent future disputes.